Start-up and hiring practices of immigrant entrepreneurs: An empirical study from an evolutionary psychological perspective - Yang, Chulguen; Colarelli, Stephen M; Han, Kyunghee; Page, Robert A (International Business Review, 2011)
Strong social ties embedded in ethnic communities of immigrant populations have been considered key assets for immigrant entrepreneurs. However, little research has been done on how biological kinship and the biological theories of altruism influence the behavior of ethnic entrepreneurs. In this study, we have applied a neo-Darwinian evolutionary theory of kinship to examine adaptive functions of kin and ethnic altruism in business start-up and hiring practices of Korean immigrant entrepreneurs in the United States. We confirmed that the patterns of help received by Korean entrepreneurs for business start-ups were congruent with an evolutionary perspective on altruism. However, the results for hiring patterns suggested that customer ethnicity trumped kin and co-ethic interests. We close by offering suggestions for future research. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Ethnic nepotism; Evolutionary psychology; Immigrant entrepreneurship; Inclusive fitness theory; Kin altruism; dept.mgt